Analisis Kondisi Eksisting Air Minum Di Kecamatan Pangkalan Kuras, Kabupaten Pelalawan - Maulidya, Syukri; Asmura, Jecky; Andrio, David (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The fulfillment of drinking water needs in Pangkalan Kuras District comes from ground water, bottled water, and river water, of which quality and quantity are not guaranteed according to PERMENKES No. 492/2010. condition of the quality of the quantity of drinking water for the people of Pangkalan Kuras District. The largest source of drinking water used by the community is well water with a percentage of 54.4%, bottled water 45.15%, and the least used is river water by 0.41%. The groundwater in Pangkalan Kuras District is still affected by peat soils, so that the groundwater feels brackish, colored and smells of mud, therefore it needs much deeper drilling to get clean water. While the bottled water used is good for consumption, the quantity and continuity have not been fulfilled because the population density is not evenly distributed in Pangkalan Kuras District. Meanwhile, river water is not of good quality if it is directly used as a source of drinking water.Keyword: Pangkalan Kuras, Drinking Water, Ground Water, Bottled Water, River Water